The Experience Logic as a New Perspective for Marketing Management From Theory to Practical Applications in Different Sectors (International Series in Advanced Management Studies,, 2018)
This book provides stimulating insights into the ways in which the adoption of experience logic can revitalize marketing perspectives and stimulate novel approaches to the creation and delivery of value. The first part of the book, which has a theoretical focus, reviews the international literature and offers conceptual observations on the experiential perspective. Suggestions are made on how experience logic can act as a new driver for the management of marketing processes in firms within the context of the experience economy. In the second part of the book, attention turns to the applications of experience logic in different sectors, including tourism, commerce, culture, and trade shows. Company-specific examples of benefits of the experiential approach are also explored in case studies on gift box providers, marketing of traditional local products, and the cosmetics industry. The book will be of particular interest for marketing specialists, but will additionally be of value for managers in private companies and public bodies who wish to enhance their marketing methods.